FRI0073 The Effect of Antirheumatic Therapy Administered in Accordance with "Treat to Target" Principles on Cardiovascular Risk in Patients with Early Rheumatoid Arthritis During 18-Month Follow-Up. (9th June 2015) - Novikova, D.S.; Popkova, T.; Kirillova, I.; Markelova, E.; Gorbunova, Y.; Karateev, D.; Luchihina, E.; Demidova, N.; Kanonirova, M.; Kasumova, K.; Lukina, G.; Vladimirov, S.; et al.
Abstract : Objectives: To assess the effect of antirheumatic therapy administered in accordance with "T2T" principles on cardiovascular risk (CVR) in early RA pts. Methods: After 18-m follow-up the CVR dynamics was assessed in 60 pts (73% of women, age 56[47;61] years) with early RA (ACR/EULAR criteria, 2010) with moderate to high activity (DAS28-5.3[5.0;6.1], positive for ACCP (100%), RF (87%) without prior administration of DMARDs, glucocorticoids. Methotrexate therapy (MT) was started in all pts with an escalation of the dose up to 30 mg/week, subcutaneously. In case of no remission 3 m later, MT was added with biologic therapy (BT): Adalimumab, Certolizumab pegol, Abatacept. After 18 m, 27 (45%) pts achieved remission (DAS28<2.6). 15 (56%) pts with remission were on MT, 12 (44%) pts - MT+BT. Among pts without remission 13 (39%) were administered MT, 20 (61%) - MT+BT. The assessment of TRF of CVD, carotid artery atherosclerosis (CAA) by data of duplex scanning and coronary artery calcinosis (CAC) by data of multispiral computer tomography was conducted in all pts. Results: The incidence rate of CHD (18%vs18%), AH (62%vs68%), overweight (55%vs63%), abdominal obesity (67%vs67%), physical inactivity (48%vs39%), smoking (17%vs17%), DM type 2 (8%vs8%) did not change significantly. An increase in HDL level was observed by 12% (from 1.37[1.03;1.69] to 1.54[1.25;1.94], p<0.005, BMI by 5% (from 26.0[22.3;30.1] to 27.2[23.1;31.2], p<0.001, a decrease in atherogenicity index by 51% (from 3.86[3.08; 5.01] to 2.55[1.60;3.40], p<0.001. A change in HDL levels correlated negatively with dynamics of DAS 28, CRP, ESR (r=-0.4, p<0.05), BMI - with CRP, ESR (r=-0.3, p<0.05). Rising of summarized CVR by SCORE (from 1.30[0.26;2.90] to 1.67[0.45;3.13], p<0.005) and SCORE≥5% (from 0% to 12%, p<0.02) was also observed. The increase in CAA rate was recorded from 67% to 73% without dynamics in carotid artery intima-media thickness. The increase in the rate of CAC was noted from 42% to 48% with dynamics of coronary calcium index (CCI) from 55[20;142] to 70[50;241], p<0.005. Rising of CVR by SCORE (from 1.52[0.45;2.90] to 2.26[0.68;3.77], p<0.005 and SCORE≥5% (from 0% to 19%, p<0.05) was noted only in pts receiving MT+BT, and among pts receiving MT no CVR dynamics by SCORE (from 0.76[0.02;1.59] to 1.15[0.02;2.06] and SCORE≥5% (from 0% to 4%) was recorded. In pts with RA remission (n=27), no new cases of CAA and CAC were recorded (0%), but in pts without remission (n=33) the incidence rate of CAA and CAC increased by 14% (p<0.05). New cases of CAA developed only in cases without remission and without statins administered. An increase in CCI was noted both in pts achieved remission (by 27%, p<0.005) and without remission (by 47%, p<0.005) irrespective of administration of statins. Conclusions: Therapy of early RA pts in accordance with "T2T" principles contributes to deceleration but not complete cessation of atherosclerosis advancement in case of achieved remission. To decrease CVR in RA pts, more precise criteria of assessment of remission and more aggressive administration of cardioprotective drugs should be applied. Disclosure of Interest: None declared